Comparative Studies of Fibrinolytic Inhibitors in Vitro - Maki, M; Beller, F. K (Thrombosis and Haemostasis, 1966)
EACA, AMCHA, Trasylol and Soya bean trypsin inhibitor were compared in regard to their inhibition potency as enzyme and activator inhibitors in vitro, in different test systems. The ratio in all systems for Trasylol and STI was 1:4/6 depending on the test system used. Both substances are only slightly less active as activator inhibitors than as plasmin inhibitors. The difference however, is so small that Trasylol as well as STI can be regarded as good activator inhibitors in vitro. Both substances inhibit plasmin as well as activator competitively and differ therefore with EACA and AMCHA.EACA and AMCHA are activator inhibitors and considerably less inactive in regard to plasmin inhibition. The already known fact that EACA inhibits the activator competitively was confirmed for AMCHA. The latter substance is 6-8 times more potent, than EACA.EACA, AMCHA, Trasylol and STI given in combination resulted in an additive or synergistic action, rather than a potentiating one as has been described in vivo.